Biological Factors Related to Distress of Patients with Diabetes Type-2 - Anita, Diyah Candra; Prihatiningsih, Dwi (International Journal of Human and Health Sciences (IJHHS), 2019)
Objective: The purpose of this study was to analyze the relationship between biological factors with distress of diabetes type 2. Material and Methods: The research method is quantitative correlation. Samples were taken by accidental sampling method for 3 months (November 2017-January 2018) in 44 patients who were treated at PKU Muhammadiyah Yogyakarta Hospital and PKU Muhammadiyah Bantul Hospital in Yogyakarta, Indonesia. The instruments of the study were medical records, diabetes distress scale (DDS17) questionnaire, sphygmomanometer, scales, and microtoise. Data analysis used was ordinal logistic regression. Result and Discussion: The results of the study showed 70.5% respondents were hyperglycemic; 79.5% respondents had normal total cholesterol; 45.5% respondents had normal HDL cholesterol; 52.3% respondents had normal LDL cholesterol; 63.6% respondents had normal triglycerides; 68.2% respondents had a normal BMI; 63.6% respondents had comorbidities; 50.0% respondents had complications; 72.7% respondents suffer from hypertension; and 68.2% respondents suffer from DM> 5 years. The result also showed 50.0% respondents had mild distress; 43.2% respondents had moderate distress; and 6.8% had severe distress. Conclusion: It was concluded that biological factors related to distress were comorbidities, complications, BMI and total cholesterol. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 207-217